Determinants of Burnout among Academic Staff of Public Universities in Southwest, Nigeria - Ajayi, Olugbenga Solomon; Azeez, Razaq Olugbenga; Olagunju, Olukayode Philip (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024DO - 10.58709/niujhu.v9i2.1903, 2024)
This study investigated determinants of burnout among academic staff of public universities in Southwest, Nigeria. Eight hundred and twenty-seven (827) academic staff were randomly selected from public universities in Southwest Nigeria. Biographical Data Form (BDF), Maslach Burnout Inventory-Human Services Survey (MBI-HSS; α = 0.90), Job Content Questionnaire (JCQ; α= 0.79), Work Environment Questionnaire (WEQ; α = 0.72) were used for data collection. Multiple Regression Analysis technique was used for data analysis Findings showed that the three organizational variables predictor (job demand, job decision latitude and work environment) compositely and independently predicted the burnout. Findings also showed that job decision latitude was the main contributor to the prediction of burnout of academic staff of public universities. The study concluded that university academic staff members are not immune to burnout and other-work related challenges affecting workers generally. The implications of the findings for stakeholders interested in effective functioning and general wellbeing of workers in the workplace – employees, employers, policy makers, and government - were discussed. Keywords: Job Demand, Job Decision Latitude, Work Environment, Burnout, Academic staff